2021
DOI: 10.5194/mr-2-653-2021
|View full text |Cite
|
Sign up to set email alerts
|

A novel multinuclear solid-state NMR approach for the characterization of kidney stones

Abstract: Abstract. The spectroscopic study of pathological calcifications (including kidney stones) is extremely rich and helps to improve the understanding of the physical and chemical processes associated with their formation. While Fourier transform infrared (FTIR) imaging and optical/electron microscopies are routine techniques in hospitals, there has been a dearth of solid-state NMR studies introduced into this area of medical research, probably due to the scarcity of this analytical technique in hospital faciliti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 52 publications
(69 reference statements)
2
12
0
Order By: Relevance
“…For COM, using a homonuclear decoupling pulse sequence (DUMBO), the 1 H NMR spectrum was recorded, showing only one signal centered at 5.26 ppm at room temperature, which was attributed to an averaging of the water molecules’ 1 H resonances. 37 Upon lowering the temperature to 100 K, four proton environments could be resolved using a heteronuclear NMR experiment (FSLG-HETCOR 1 H– 13 C), which is consistent with the crystallographic data (i.e., two inequivalent water molecules). 37 Recently, 1 H NMR has also been used to analyze crystalline phases of the calcium oxalate minerals present in kidney stones: 37 it was demonstrated that T 2 * edited 1 H and 1 H– 1 H double-quantum (DQ) NMR experiments can be used to separate the organic and mineral parts within stones, showing them to be more insightful than the routinely used IR spectroscopy.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…For COM, using a homonuclear decoupling pulse sequence (DUMBO), the 1 H NMR spectrum was recorded, showing only one signal centered at 5.26 ppm at room temperature, which was attributed to an averaging of the water molecules’ 1 H resonances. 37 Upon lowering the temperature to 100 K, four proton environments could be resolved using a heteronuclear NMR experiment (FSLG-HETCOR 1 H– 13 C), which is consistent with the crystallographic data (i.e., two inequivalent water molecules). 37 Recently, 1 H NMR has also been used to analyze crystalline phases of the calcium oxalate minerals present in kidney stones: 37 it was demonstrated that T 2 * edited 1 H and 1 H– 1 H double-quantum (DQ) NMR experiments can be used to separate the organic and mineral parts within stones, showing them to be more insightful than the routinely used IR spectroscopy.…”
Section: Introductionsupporting
confidence: 71%
“… 37 Upon lowering the temperature to 100 K, four proton environments could be resolved using a heteronuclear NMR experiment (FSLG-HETCOR 1 H– 13 C), which is consistent with the crystallographic data (i.e., two inequivalent water molecules). 37 Recently, 1 H NMR has also been used to analyze crystalline phases of the calcium oxalate minerals present in kidney stones: 37 it was demonstrated that T 2 * edited 1 H and 1 H– 1 H double-quantum (DQ) NMR experiments can be used to separate the organic and mineral parts within stones, showing them to be more insightful than the routinely used IR spectroscopy. 37 Lastly, 13 C NMR (spin-1/2 nucleus of moderate receptivity, γ = 6.7281 × 10 7 rad s –1 T –1 ) studies on COM have shown that the NMR signature of this nucleus is particularly sensitive to temperature, as attested by the changes in the resolution of the four peaks belonging to the two inequivalent oxalate ions, and 13 C was further used to follow structural transformations from COT to COM.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations